Investigating the role of some folate biosynthesis pathway enzymes in survival of escherichia coli - Dina Samir Rasmi; Ramy Karam Aziz; Yomna Abdelawad Hashem (Cairo : Dina Samir Rasmi, 2019)
Folate biosynthesis in bacteria has been extensively studied, but the essentiality of one of the steps in the pathway, dihydroneopterin triphosphate (DHNTP) hydrolysis to dihydroneopterin monophosphate (DHNMP), is yet to be demonstrated. A candidate enzyme catalyzing this step, dihydroneopterin hydrolase, was confirmed to affect folate biosynthesis; however, the deletion of its encoding gene, ntpA, does not result in bacterial lethality. Computational modeling suggests the possibility that other phosphatases such as mutT or the broad-spectrum phoA may be compensating for the loss of ntpA. To investigate the role of these two genes, we constructed, in Escherichia coli K-12 MG1655, single, double and triple mutants lacking mutT or phoA, in addition to ntpA. Growth experiments were conducted on the wild type and mutant strains. The triple mutant, xmutTxntpAxphoA, failed to grow on M9 minimal media, which suggests that mutT, ntpA and phoA together are essential for the bacterial growth in minimal media, while the growth of the double mutant,xmutTxntpA, was significantly slower. Quantitative reverse-transcription PCR (qRT-PCR) indicated that the expression of phoA and mutT, but not that of ntpA, significantly increased in response to sub-minimal inhibitory concentrations of sulfonamides, confirming the involvement of the genes in the folate pathway. More transcriptional analysis was performed on the single and double mutants to study the expression of each gene in absence of its putative complementary one(s), but there was no significant upregulation at the gene expression level. For a better understanding of the function of the three genes, transcriptomic data from the Gene Expression Omnibus (GEO) resource were analyzed to determine how different conditions might affect the expression of the ntpA, mutT and phoA in E. coli K-12. Subsequently, qRT-PCR was used to confirm these computational predictions. Culture density increase was demonstrated to decrease the expression of ntpA, mutT while increasing phoA expression
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: DHNTPase; Folate pathway; ntpA